In‐Situ Stabilizing Nano‐Ag onto Nonwoven Fabrics via a Mussel‐Inspired Approach for Continuous‐Flow Catalysis Reduction of Organic Dyes. Issue 6 (9th February 2022) - Sha, Zhou; Fan, Jiahui; Lu, Jian; He, Huan; Hong, Bo; Fei, Xiang; Zhu, Meifang
Abstract: A novel nonwoven‐fabric‐supported‐nano‐Ag (NWF/Ag) reactor was obtained via a mussel‐inspired in‐situ fabrication method. The resulting NWF/Ag features a high catalytic activity for the reduction reaction of organic dyes in the presence of sodium borohydride. More importantly, it is also feasible for the scale‐up catalysis in NWF/Ag‐assembled continuous‐flow reactors. Such a NWF/Ag catalyst preserves the fiber‐based three‐dimensional architecture to effectively drive the continuous‐flow catalysis reactions at unprecedented efficiency, benefiting from it the easy diffusion of dye molecules to access the active catalytic sites of nano‐Ag. Moreover, the resulting NWF/Ag composites can serve as versatile platforms to assemble continuous‐flow reactors in different shapes, sizes, and configurations to extend the catalysis applications. In this study, the catalytic reduction conversion of methylene blue can reach more than 98 % in 270 seconds using the NWF/Ag‐based channel‐type continuous‐flow reactor. It also preserves good catalytic reduction performance to other organic dyes, including methyl orange and acid orange 7. The NWF‐based platforms, combined with a rational designed approach of surface functionalization and hybridization, probably provide new insights into the catalytic reduction of organic dyes in a continuous‐flow way. Abstract : A novel nonwoven‐fabric‐supported‐nano‐Ag (NWF/Ag) composite was fabricated via a mussel‐inspired in‐situ reduction approach, which features a high catalytic activity for the reduction reaction of organic dyes in the presence of sodium borohydride. It can further serve as versatile platforms to assemble versatile continuous‐flow reactors for catalytic reduction of organic dyes with high catalytic performance. Such NWF‐based platforms probably provide new insights into the catalytic reduction of organic dyes in a continuous‐flow way.